Multipotent mesenchymal stromal cells: A promising strategy to manage alcoholic liver disease - Ezquer, Fernando (World J Gastroenterol, 2016)
Chronic alcohol consumption is a major cause of liver disease. The term alcoholic liver disease (ALD) refers to a spectrum of mild to severe disorders including steatosis, steatohepatitis, cirrhosis, and hepatocellular carcinoma. With limited therapeutic options, stem cell therapy offers significant potential for these patients. In this article, we review the pathophysiologic features of ALD and the therapeutic mechanisms of multipotent mesenchymal stromal cells, also referred to as mesenchymal stem cells (MSCs), based on their potential to differentiate into hepatocytes, their immunomodulatory properties, their potential to promote residual hepatocyte regeneration, and their capacity to inhibit hepatic stellate cells. The perfect match between ALD pathogenesis and MSC therapeutic mechanisms, together with encouraging, available preclinical data, allow us to support the notion that MSC transplantation is a promising therapeutic strategy to manage ALD onset and progression.